2017
DOI: 10.1001/jamasurg.2016.5049
|View full text |Cite
|
Sign up to set email alerts
|

Undertriage of Firearm-Related Injuries in a Major Metropolitan Area

Abstract: Undertriage of firearm-related injuries was much more prevalent than expected. Although the likelihood of dying during hospitalization was greater among patients treated in designated trauma centers, these patients were substantially in worse condition across all measures of injury severity. A smaller proportion of patients treated in designated trauma centers died during the first 24 hours of hospitalization. This study highlights the need for better regional coordination, especially with interhospital transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Based on prior research we expected to find some evidence linking the distance to a trauma center with victim survival (Crandall, et al, 2013;Sall et al, 2018;Circo 2019). Indeed, a wealth of studies have illustrated the importance that specialized trauma care plays for critically injured individuals (Lale, Krajewski, & Friedman, 2017). With improvements in medicine, surgery, and trauma care, gunshot wound victims have increasingly better outcomes (Manley, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on prior research we expected to find some evidence linking the distance to a trauma center with victim survival (Crandall, et al, 2013;Sall et al, 2018;Circo 2019). Indeed, a wealth of studies have illustrated the importance that specialized trauma care plays for critically injured individuals (Lale, Krajewski, & Friedman, 2017). With improvements in medicine, surgery, and trauma care, gunshot wound victims have increasingly better outcomes (Manley, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many of these underserved areas were distributed on Chicago's South-East side, suggesting a need for increased access (Wandling, et al, 2016). A further follow-up study in Chicago found that nearly 30% of gunshot wound victims were treated in a non-designated trauma center -what the authors classified as "under-triage" (Lale, Krajewski, & Friedman, 2017). This research suggested that lack of access to appropriate care could lead to worse outcomes among victims.…”
Section: Urban Gun Violence Trauma Centers and Victim Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, feedback loops are often weak for emergency medicine physicians, who do not routinely get follow-up information on patient outcomes, particularly for those transferred to another facility for definitive management or aftercare ( 7 ). As evidence of these challenges, diagnostic errors persist despite decades of continuing medical education efforts ( 5 11 ).…”
mentioning
confidence: 99%
“…However, undertriage occurs with representative cases as well. For example, Lale et al ( 9 ) found that 90% of Chicago-area patients with penetrating injuries (a feature representative of severe injury) taken to nontrauma centers were kept at that facility and not transferred to a higher level of care. As a result, successful interventions could improve performance all around.…”
mentioning
confidence: 99%